Thinking, Walking, Talking: Integratory Motor and Cognitive Brain Function - Leisman, Gerry; Moustafa, Ahmed A.; Shafir, Tal (Frontiers in Public Health, 2016)
In this article, we argue that motor and cognitive processes are not separate, but most likely share similar evolutionary history. This is supported by clinical and neural data showing that some brain regions play a similar function in both motor and cognitive functions. In addition, we also argue that cognitive processes play a role for the generation of complex motor output, which is supported by data from patients with stroke and Parkinson’s disease. Further, we also review data that motor processes can contribute to cognitive function, as found by many training programs. Thus, motor and cognitive processes have dynamical bidirectional relationships, which we explain here.